2020
DOI: 10.1111/crj.13182
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumour effects of Keratin 6A in lung adenocarcinoma

Abstract: BackgroundTo examine the effects of Keratin 6A (KRT6A) protein on the proliferation, migration and invasion abilities of lung adenocarcinoma cells, and to analyse the relationship between the expression level of KRT6A protein and the survival prognosis of lung adenocarcinoma patients.MethodsWestern Blot was used to detect the expression of KRT6A protein in lung adenocarcinoma cell lines. CCK‐8 experiment and colony formation assays were performed to detect the proliferation ability. Wound healing assay and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Through clinical analysis, we found that the elevated expression of KRT6A can be used as a risk factor for predicting the survival outcome of NSCLC patients. Interestingly, another study confirmed our finding by showing that KRT6A inhibits the proliferation and invasion of lung adenocarcinoma cells, and high expression of KRT6A protein may be a prognostic marker for patients with lung adenocarcinoma ( Xiao et al, 2020 ). Therefore, deeper investigations are warranted to explore the function of KRT6A in lung cancer progression.…”
Section: Discussionsupporting
confidence: 82%
“…Through clinical analysis, we found that the elevated expression of KRT6A can be used as a risk factor for predicting the survival outcome of NSCLC patients. Interestingly, another study confirmed our finding by showing that KRT6A inhibits the proliferation and invasion of lung adenocarcinoma cells, and high expression of KRT6A protein may be a prognostic marker for patients with lung adenocarcinoma ( Xiao et al, 2020 ). Therefore, deeper investigations are warranted to explore the function of KRT6A in lung cancer progression.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, LAMC2 promotes the chemotactic function of granulocytes ( 53 , 54 ); DSC2 correlates positively with adhesion, migration, and infiltration of granulocytes ( 55 , 56 ); and KRT6A protein inhibits the proliferation, migration and invasion abilities of lung cancer cells. The high expression of KRT6A protein is related to good prognosis in patients with lung adenocarcinoma ( 57 ); FOSB protein plays an anti-tumor role in lung cancer ( 58 ). These results indicated that ginsenoside Rg1 significantly inhibited the mRNA expression of ARG2, MMP1, S100A4 , and RAPSN in granulocytes inhibited by NA and, simultaneously, significantly elevated the mRNA expression of LAMC2, DSC2, KRT6A , and FOSB .…”
Section: Resultsmentioning
confidence: 99%
“…The peptides from the C-terminal region of the protein show antimicrobial activity against bacterial pathogens. KRT6A protein inhibits the proliferation, migration and invasion abilities of lung adenocarcinoma cells, and high expression of KRT6A protein is a predictor of good prognosis in patients with lung adenocarcinoma ( 57 ). Neutrophils could directly kill tumor cells by releasing NO ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing KRT6A has been demonstrated to inhibit invasion and metastasis in nasopharyngeal cancers [34]. However, its role in lung adenocarcinoma is somewhat ambiguous, with varying reports suggesting that it may act as both an oncogene and a tumor suppressor [34,35].…”
Section: Discussionmentioning
confidence: 99%